2019
DOI: 10.1073/pnas.1813026116
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation of core components of the translation initiation machinery regulates protein synthesis

Abstract: Protein synthesis is essential for cell growth, proliferation, and survival. Protein synthesis is a tightly regulated process that involves multiple mechanisms. Deregulation of protein synthesis is considered as a key factor in the development and progression of a number of diseases, such as cancer. Here we show that the dynamic modification of proteins by O-linked β-N-acetyl-glucosamine (O-GlcNAcylation) regulates translation initiation by modifying core initiation factors eIF4A and eIF4G, respectively. Mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 51 publications
(58 reference statements)
2
44
0
Order By: Relevance
“…By quantifying how much each OGT activity impacts the abundance of each protein in the cell, we have identified the biological pathways most affected by each OGT activity. Consistent with known roles for O-GlcNAc, we found that Ser/Thr glycosylation broadly regulates metabolism and gene expression, with enriched pathways including splicing (44), translation (69)(70)(71), and autophagy (72)(73)(74). Among the pathways linked to OGT's noncatalytic activities are oxidative phosphorylation, the electron transport chain, and components of the actin cytoskeleton, consistent with prior data suggesting OGT binds to the actin-regulating Ecadherin/beta-catenin complex (39).…”
Section: Discussionsupporting
confidence: 86%
“…By quantifying how much each OGT activity impacts the abundance of each protein in the cell, we have identified the biological pathways most affected by each OGT activity. Consistent with known roles for O-GlcNAc, we found that Ser/Thr glycosylation broadly regulates metabolism and gene expression, with enriched pathways including splicing (44), translation (69)(70)(71), and autophagy (72)(73)(74). Among the pathways linked to OGT's noncatalytic activities are oxidative phosphorylation, the electron transport chain, and components of the actin cytoskeleton, consistent with prior data suggesting OGT binds to the actin-regulating Ecadherin/beta-catenin complex (39).…”
Section: Discussionsupporting
confidence: 86%
“…For example, O-GlcNAc modifications have been shown previously to regulate the cell cycle and play a crucial role in PI3K-Akt signaling, and both of these pathways were enriched (51). Ribosomal components were also enriched and several studies have reported a link between O-GlcNAc and ribosome biogenesis and function (52-54). However, the top two enriched pathways, the spliceosome and HSV infection, have received little to no attention as pathways regulated by OGT.…”
Section: Resultsmentioning
confidence: 99%
“…Translation initiation factors are related to cell proliferation and tumorigenesis. For example, activation of eIF4F complex is involved in tumorigenesis [42,43], and glycosylation of eIF4G promotes cell proliferation [44]. Alterations in eIF3 subunit expression have been reported for many types of cancer cells, such as the overexpression of eIF3A, B, C, H, I, and M, and under-expression of eIF3E and F [45].…”
Section: Introductionmentioning
confidence: 99%